A multi-objective linear programming framework for evaluating the financial viability of supplementary facilities in Build-Transfer-Lease projects in Korea - Jung, Wooyong; Koo, Bonsang; Han, Seung Heon (KSCE Journal of Civil Engineering, 2012)
Since 2005, the Build-Transfer-Lease (BTL) scheme has been successful in delivering projects such as schools and government housing to the general public while relieving the fiscal constraints of the Korean government. Recently, the inclusion of ‘supplementary’ facilities to the main BTL project has been posited as an alternative solution to increase a BTL project’s rate of returns. However, the absence of a structured approach to evaluate the financial viability of this modified scheme has thus far made its use restrictive. Determining the viability of the modified scheme requires identifying the relative project size of the supplementary facility and the appropriation of the additional revenue between the government and concessionaire that ensure that both parties benefit, while accounting for the increased risk in liquidity. This research proposes a framework using multi-optimization linear programming and Monte Carlo simulation that determines the optimal size of the supplementary facility and the appropriate revenue distribution ratio that minimize government payments and maximize the internal rate of return, while maintaining positive project cash flows. A retrospective case study on a military housing project demonstrates that using the proposed framework enables the addition of a shopping mall which increases the overall rate of return while minimizing the risks of the project.